Maggot Production in Various Organic Wastes (Vegetables, Fruits, Food Processing Industries): Potential as Alternative Feed Substitutes for Fish Meal - Yunilas; E. Mirwandhono; Sihombing, Saur M. (Jurnal Peternakan Integratif, 2022)
Maggot is an alternative to fish meal because it has a fairly high protein content, is easy to cultivate and is able to decompose organic waste into its own food. The better the quality of the maggot growing media, the higher the maggot production will be . Vegetable, fruit and food processing industrial waste is an organic waste that is commonly encountered but its nutritional quality is low. To improve the nutritional quality, fermentation was carried out using local microorganisms (MOL). The purpose of this study was to examine the effect of various types of vegetable, fruit and food processing industrial waste media and different fermentation times on the production of maggot (Hermetia illucens). This study was conducted experimentally using factorial randomized block design (RAK) method with 2 factors ( 3Ã—3), namely factor 1 for various organic wastes (D1 = vegetable waste, D2 = fruit waste, D3 = food processing industrial waste) and factor 2 for fermentation time (L1 = 2 days, L2 = 4 days, L3 = 6 days), with 3 replicates. The parameters of this study consisted of biomass weight, feed consumption, waste reduction index/WRI, feed conversion efficiency/ECI, and survival rate/SR. The results of variance showed that organic waste and fermentation time had a very significant effect (p<0.01) on the parameters of maggot production. It was concluded that the production of maggot (Hermetia illucens) was best in the D1L1 treatment with a biomass weight of 1522.33 g, feed consumption 66.06%, WRI 2.20%, ECI 0.42%, and SR 89.52%.